Moderate aortic stenosis: culprit or bystander?. Issue 1 (24th January 2022) - Pankayatselvan, Varayini; Raber, Inbar; Playford, David; Stewart, Simon; Strange, Geoff; Strom, Jordan B
Abstract : Non-rheumatic aortic stenosis (AS) is among the most common valvular diseases in the developed world. Current guidelines support aortic valve replacement (AVR) for severe symptomatic AS, which carries high morbidity and mortality when left untreated. In contrast, moderate AS has historically been thought to be a benign diagnosis for which the potential benefits of AVR are outweighed by the procedural risks. However, emerging data demonstrating the substantial mortality risk in untreated moderate AS and substantial improvements in periprocedural and perioperative mortality with AVR have challenged the traditional risk/benefit paradigm. As such, an appraisal of the contemporary data on morbidity and mortality associated with moderate AS and appropriate timing of valvular intervention in AS is warranted. In this review, we discuss the current understanding of moderate AS, including the epidemiology, current surveillance and management guidelines, clinical outcomes, and future studies.